A Schur-Horn Type Theorem for Symplectic Matrices (Communications in Mathematical Research, 2025)
In this note, we establish a new version of Schur-Horn type theoremfor symplectic matrices. Meanwhile, we establish a necessary and sufficientcondition for the equality to hold in the above result.
Keywords: Positive definite matrix; symplectic matrix; equality; doubly stochastic matrix